2013
DOI: 10.4081/ijas.2013.e51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Storage Period on Egg Weight, Internal Egg Quality and Hatchability Characteristics of Fayumi Eggs

Abstract: In this study, hatchability characteristics and some internal egg quality characteristics of 0, 2, 3, 4, 6 and 8 d stored Fayoumi eggs were examined. It was determined that the effect of storage time on hatchability, hatchability of fertile eggs, embryonic mortality, hatchling weight, albumen weight, yolk weight, albumen index, yolk index and Haugh unit was significant (P<0.05). There was no positive or negative effect of storage time on the fertility rates, but there was a negative effect of storage time on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
26
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 30 publications
21
26
3
6
Order By: Relevance
“…Current findings were similar to results of Şekeroğlu et al (2008), Yılmaz and Bozkurt (2008), Akyürek andOkur (2009), Demirel andKırıkçı (2009), Khan et al (2013) and Raji et al (2009).…”
Section: Internal Egg Quality Traitssupporting
confidence: 81%
See 1 more Smart Citation
“…Current findings were similar to results of Şekeroğlu et al (2008), Yılmaz and Bozkurt (2008), Akyürek andOkur (2009), Demirel andKırıkçı (2009), Khan et al (2013) and Raji et al (2009).…”
Section: Internal Egg Quality Traitssupporting
confidence: 81%
“…Jones and Musgrove (2005), Şamlı et al (2005), Şekeroğlu et al (2008), Yılmaz and Bozkurt (2008) (2011), Khan et al (2013), and Okur and Şamlı (2013) carried out experiments on internal egg quality traits and reported similar findings with the present study. Contrary to those studies, Jin et al (2011) reported insignificant effects of storage durations on the Haugh unit.…”
Section: Internal Egg Quality Traitssupporting
confidence: 79%
“…Average egg weight loss (7.75%) regardless the egg size class in the study is lower than the value of 12.94% reported by Soliman et al (1994) for quail eggs. It is also lower than the values of 24.76% reported by Saylam (1999) and 20.90% reported by Saylam and Sarıca (1999) in quail eggs, and higher than the values of 1.25% reported by Khan et al (2013) in Fayoumi eggs which consequently affect the chick weight at hatching. The differences in weight losses among different studies during incubation can be due to the difference in species.…”
Section: Statistical Analysescontrasting
confidence: 51%
“…Similar results on Fayoumi chicken eggs were obtained by Khan et al, 2013. Other studies reported that prolonged storage influence egg quality due to physicochemical changes resulted in flattening of the yolk caused by the weakening of the vitelline membrane (Samli et al, 2005).…”
Section: Egg Quality Resultssupporting
confidence: 77%